2017
DOI: 10.3390/ijms18102071
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Novel Alleles and Genotype/Phenotype Correlations Resulting from the Analysis of 108 Previously Undetected Mutations in Patients Affected by Neurofibromatosis Type I

Abstract: Neurofibromatosis type I, a genetic disorder due to mutations in the NF1 gene, is characterized by a high mutation rate (about 50% of the cases are de novo) but, with the exception of whole gene deletions associated with a more severe phenotype, no specific hotspots and few solid genotype/phenotype correlations. After retrospectively re-evaluating all NF1 gene variants found in the diagnostic activity, we studied 108 patients affected by neurofibromatosis type I who harbored mutations that had not been previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
(39 reference statements)
1
13
2
Order By: Relevance
“…Seventy‐three distinct intragenic NF1 variants found in the current study have a similar distribution pattern found in previous studies thus confirming the absence of hot‐spot regions (Barrea et al., 2018; Bonatti et al., 2017; Kang et al., 2020; Terzi et al., 2007). According to previous studies, most of the germline pathogenic NF1 variants appear to cause truncation of the gene product, often by altering mRNA splicing (Friedman, 1993; Palma Milla et al., 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Seventy‐three distinct intragenic NF1 variants found in the current study have a similar distribution pattern found in previous studies thus confirming the absence of hot‐spot regions (Barrea et al., 2018; Bonatti et al., 2017; Kang et al., 2020; Terzi et al., 2007). According to previous studies, most of the germline pathogenic NF1 variants appear to cause truncation of the gene product, often by altering mRNA splicing (Friedman, 1993; Palma Milla et al., 2018).…”
Section: Discussionsupporting
confidence: 91%
“…A total of 309 NF1 patients were selected on the basis of the inclusion and exclusion criteria and included in the study; 255 were recruited from the authors' institutions (92 with OPG and 163 without OPG) and 54 were retrieved from the recent literature (40 with OPG and 14 without OPG) [33][34][35][36][37][38][39][40][41]. One hundred and thirty-two patients were included in the NF1 OPG group (61 females, 57 males; the sex of 14 patients retrieved from the literature was not reported) and 177 in the NF1 non-OPG group (91 females, 76 males; 10 unknown).…”
Section: Resultsmentioning
confidence: 99%
“…The literature review allowed us to select 54 patients; there were more patients in the OPG group (40) than in the non-OPG group (14) [33][34][35][36][37][38][39][40][41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, identification and providing information of pathologic mutations are important, even more to sporadic patients who are usually diagnosed later than familial cases. Besides the direct-sequencing method of genomic DNA, supplementary tests (reverse transcription PCR of total RNA, MLPA, FISH), which have been used in the present study, can be helpful to identify specific genotypes of patients [ 20 , 24 , 25 ]. The ongoing recognition of different mutations may give insights into the still unknown mechanisms involved in the development of NF1, allowing further genotype-phenotype correlations.…”
Section: Discussionmentioning
confidence: 99%